"How Dare You!" African American Faculty and the Power Struggle With White Students. (December 2020) - Thomas, Vanessa
Higher education institutions are hiring more Intellectuals of Color to diversify their faculty. However, the diverse faculty presents an adverse dynamic between White male students and Black female professors. White students tend to exhibit disruptive, intimidating behavior toward Black faculty. Historical stereotypes, prejudices, biases, racism, oppression, and White supremacist attitudes and beliefs displayed in society express itself in the classroom. Black faculty face unique challenges in comparison with their White colleagues when teaching White students. White students more frequently disrespect and challenge the competency of Black faculty while disrupting the classroom learning environment. Meanwhile, Black faculty must display a high level of emotional labor to cope with the daily stressors.